FAKTOR YANG BERHUBUNGAN TENTANG P4K DENGAN KESIAPAN PERSALINAN DI KELURAHAN PARUPUK TABING TAHUN 2017 - Abdi Iswahyudi Yasril (Universitas Fort De Kock, 2019)
The Birth Prevention and Complication Prevention (P4K) Program is performed because of the complication and AKI tillage. Based on the Health Profile of West Sumatra, the 2015 complication is 58.0%. Padang City is one of West Sumatera Province which has 33,10% complication from 22 healtcare. The purpose of this research is to know the relation of knowledge, attitude of pregnant mother and husband support about P4K with the readiness of delivery in Parupuk Tabing Urban Village in 2017. This research use crossectional design with proportional sampling technique. The object in this research is pregnant women in Parupuk Tabing urban district. To know the relationship of knowledge, attitude and support of husband about P4K with the laborreadiness is tested by Chi-Square test with degree of trust 95%. The statistical test showed that there is a correlation between mother's knowledge level (p = 0,046), attitude (p = 0,048) and husband support (p = 0,001) to P4K with the readiness of labor. It was concluded that there was a relationship of knowledge, attitude of pregnant mother about P4K with the readiness of persalian. To the husband is expected to take the time to accompany the mother to examine her pregnancy, and provide support to prepare for delivery according to P4K Program..